Prevalence of asthma in Finnish young men. Issue 6746 (4th August 1990) - Haahtela, T; Lindholm, H; Björkstén, F; Koskenvuo, K; Laitinen, L A
Abstract : OBJECTIVE–To determine the prevalence of asthma in cohorts of Finnish young men in the period 1926-89. DESIGN–A retrospective analysis using reports and statistics of Finnish defence forces. SETTING–Call up examinations of candidates for military conscription and examination of conscripts discharged because of poor health. SUBJECTS–Roughly 900, 000 men–that is, 98% of men of conscription age–examined in 1966-89 and a proportional but unknown number examined in 1926-61. MAIN OUTCOME MEASURES–Asthma recognised at call up examination, exemption from military service, and discharge from military service because of asthma. RESULTS–During 1926-61 the prevalence of asthma recorded at call up examinations remained steady at between 0.02% and 0.08%. Between 1961 and 1966, however, a continuous, linear rise began, the prevalence increasing from 0.29% in 1966 to 1.79% in 1989–that is, representing a sixfold increase. Compared with 1961 the rise was 20-fold. From 1966 to 1989 the sum of exemptions and discharges from military service due to asthma increased analogously sixfold. CONCLUSIONS–If the apparent increase in asthma detected in Finnish young men was due entirely to improved diagnostic methods and other confounding effects then some 95% of cases must have gone undiagnosed in the years before 1966. This seems inconceivable, which suggests that much of the increase was real. This conclusion is strengthened by the observed rise in exemptions and discharges due to asthma.